Inisiasi Optimalisasi Fungsi Perencanaan Manajer Pelayanan Keperawatan Unit Layanan Home Health Care - Yiyin Qamariah Takaredas; Hanny Handiyani; Dewi Gayatri; Ati Surya Mediawat; Masfuri Masfuri (Journal of Telenursing (JOTING), 2023)
This study aims to optimize the nurse manager's planning function based on identifying needs or solving problems in the service unit. The method used is a case report by conducting interviews, observing using observation sheets, and distributing questionnaires. The study results show optimizing the planning function of nurses as managers of nursing services. Preparation of draft Guidelines and SPO for home health care services is a solution. Implementation is carried out through Lewin's three phases process planned change approach. In conclusion, nurses need to show that nurses have a responsibility to ensure patient safety with adequate competence, including by maximizing the function of nurses as managers of nursing services by optimizing the planning function of nurse managers. Keywords: Home Health Care, Optimization, Nurse Manager